Extension Approaches and Advisory Services for Climate Smart Livestock (CSL): An Overview - Prabex, Salam Prabex; Meena, Hans Ram; Chander, Mahesh; Srikanth, Vallabhaneni; Saran, Vimla (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Climate Smart Livestock (CSL) farming is a collection of different technical solutions to reduce the impact of climate change on  livestock and vice versa. They include both mitigation and adaptation strategies, which will sustainably increase cattle productivity,  offer adaptability, and reduce greenhouse gas emissions while ensuring food security. The role of extension and advisory services  is essential for sustainable climate-smart livestock farming as well as combating climate change in developing countries like India,  where the majority of livestock farmers are marginal to small, as these services are key in creating awareness, motivating adoption,  and facilitating the implementation of suitable practices and technologies. Extension providers can play a major role in supporting  climate-smart farming through technology development and information dissemination, strengthening farmer’s capacity, facilitation  and brokering, and advocacy and policy support. In this context, the article covers CSL and its essential adoption needs, Extension  approaches for CSL, and CSL and rural advisory services.
Keywords: Climate Change; Climate-Smart Villages; Extension and advisory services; Livestock Calendar